2019
DOI: 10.1038/s42003-019-0527-y
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor transformation elicits systematic patterns of activity along the dorsoventral extent of the superior colliculus in the macaque monkey

Abstract: The superior colliculus (SC) is an excellent substrate to study sensorimotor transformations. To date, the spatial and temporal properties of population activity along its dorsoventral axis have been inferred from single electrode studies. Here, we recorded SC population activity in non-human primates using a linear multi-contact array during delayed saccade tasks. We show that during the visual epoch, information appeared first in dorsal layers and systematically later in ventral layers. During the delay peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 64 publications
6
43
0
Order By: Relevance
“…This layered structure, located at the roof of the brain stem, plays a critical role in transforming sensory information into eye movement commands. Population recordings have been successfully performed in the SC using linear probes [91], and it thus might be possible to identify dominant patterns of neural activity in SC using dimensionality reduction [71]. Our results predict that slow drift in the cortex should be significantly correlated with slow drift in the SC.…”
Section: Discussionmentioning
confidence: 73%
“…This layered structure, located at the roof of the brain stem, plays a critical role in transforming sensory information into eye movement commands. Population recordings have been successfully performed in the SC using linear probes [91], and it thus might be possible to identify dominant patterns of neural activity in SC using dimensionality reduction [71]. Our results predict that slow drift in the cortex should be significantly correlated with slow drift in the SC.…”
Section: Discussionmentioning
confidence: 73%
“…6, 7), this notion did not hold up. Instead, all three cell populations (V, VM, M) showed similar T-G transitions, consistent with extensive sharing of information along the dorsal-ventral layers of the SC (Massot et al, 2019). It therefore appears that the reason V cells mainly coded Te was simply because (by definition) they were more active early in the transformation, whereas M cells coded G because they were mainly active later in the response.…”
Section: Spatial Coding In Different Sc Cell Types: Fixed or Dynamic?mentioning
confidence: 74%
“…Alternatively, it has been demonstrated that the SC (and other cortical gaze areas) can provide a visual-motor transformation for gaze shifts when the experimental task introduced a temporal or spatial separation between the visual stimuli and movement initiation (Gnadt and Andersen, 1988;Everling et al, 1999;Munoz and Everling, 2004;Sadeh et al, 2015;Sajad et al, 2015). Recently, the anatomic basis for this has been demonstrated at the level of SC microcircuitry, where the visual response is transmitted from dorsal to ventral layers, the delay response is similarly distributed, but motor response recruitment proceeds in the opposite direction (Massot et al, 2019).…”
Section: Evidence For a Visual To Motor Transformation In The Scmentioning
confidence: 99%
“…However, in that study (Hafed & Chen, 2016), we did not control for the depths of the recorded neurons from the SC surface when we analyzed the neurons’ motor bursts. Since the strength of SC motor bursts can vary substantially with depth from the SC surface (Massot et al, 2019), here, I wanted to first confirm whether the asymmetry alluded to above (Hafed & Chen, 2016) was still present when carefully controlling for neuron depth (Methods). If this was the case, I could then ask whether saccade kinematics were systematically different or not.…”
Section: Resultsmentioning
confidence: 99%